A Scope Theory of Contrastive Topics - Tomioka, Satoshi (IBERIA: An International Journal of Theoretical Linguistics, 2010)
Contrastive Topics (CTs) in Japanese mimic foci more than topics in many ways. Their prosodic properties are essentially the same as the pattern found with foci, and information structurally, they can correspond to new information. In my previous work (Tomioka 2010), I argued that CTs always involve contrasted speech acts, and this paper presents further evidence for this hypothesis by closely examining how CTs and foci interact. The proposed analysis leads to a new set of questions, one of which is how a focus and a CT are distinguished when they appear simultaneously in one sentence. I argue that a focus is subjected both to the exhaustifying operation at the level of proposition and to the set-generating operation at the level of speech act whereas a CT must be spared from the exhaustification below speech act. The differentiation is achieved via the ‘selective binding’ approach to association with focus proposed by Wold (1996).